Co-influence of ultrasound and microwave in vacuum frying on the frying kinetics and nutrient retention properties of mushroom chips. Issue 15 (2nd November 2020) - Devi, Shoma; Zhang, Min; Ju, Ronghua; Mujumdar, Arun S.
Abstract: The frying kinetics (moisture loss rate and oil uptake rate) of an innovatively designed ultrasound and microwave-assisted vacuum frying (UMVF) system was investigated and the possibility of UMVF for reducing the nutrient losses during frying were evaluated in this work. The white button mushroom was the tested sample in this study. The chips were fried into two frying temperatures (80 and 90 °C), three different frying processes, vacuum frying (VF), microwave vacuum frying (MVF), and UMVF at a fixed vacuum pressure (12 ± 1 kPa). The first-order kinetic model was used for the mass transfer (moisture loss and oil uptake). Concerning the fitting performances, the logarithmic model and Pedrischi model showed the best-fitted model for moisture loss rate and for oil uptake respectively. Combining ultrasound and microwave in VF, the calculated moisture diffusivity rate was increased from 1.599 × 10 −10 to 2.769 × 10 −10 m 2 /s and oil uptake rate was decreased from 0.0121 to 0.0059 s −1 . Total oil content (TOC) of fried mushroom chips (FMC) was quantified into two segments, surface oil (SO), and structure oil (STO) at a different time interval during frying. STO had the highest fraction of TOC and results revealed that UMVF had significantly low level of STO, which means UMVF helped to reduce the oil absorption during frying. In order to consider the nutrient retention values, UMVF exhibited the highest nutrition retention values. The exponential spectra of LF-NMR clearly revealed the water–oil distribution of FMC.